Tribo-spectral method and identification of the micromechanical characteristics of the exfoliated graphite based materials - Nikitin, Yu. A.; Zaporozhets, V. V.; Chernysh, I. G. (Proceedings of National Aviation University (archive), 2003)
The results obtained in the experiments allow us to demonstrate the successful application o f the tribospectralmethod deforming and tribo-spectrum analysis fo r the identification o f tribo-spectral characteristicso f lightweight exfoliated graphite based materials in the wide range o f their density. This undoubtedly a favorin upgrading o f the quality o f the control o f both technological processes o f lightweight powder material productionand property degradation processes in materials and products. Some parameters o f the tribospectralcharacteristics may be used as a criterion fo r a comparative estimation o f the powdered materialproduction, that may be exploited in order to increase the efficiency o f the moulding materials qualitycontrol. Tribo-spectral method can be usedfor the estimation o f oxide stability’ o f lightweight materials fo r theoptimization o f the composite material content. Tribo-spectral characteristics are sensitive to the processes o fthermo-oxide destruction o f the structure and can be appliedfor the optimization o f the content ofparts madeo f the lightweight graphite composite materials